Radiological “Teddy Bear” Sign on CT Imaging to Aid Internal Carotid Artery Localization in Transsphenoidal Pituitary and Anterior Skull Base Surgery - Yeung, W.; Twigg, V.; Carr, S.; Sinha, S.; Mirza, S. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objectives Internal carotid artery (ICA) injury remains a rare but potentially fatal complication of transsphenoidal pituitary or anterior skull base surgery. Preoperative imaging must be scrutinized to minimize risk. On axial computed tomography (CT), the protrusions of the ICAs into the sphenoid resemble a “teddy bear.” This article aims to describe the sign, its grading system (0–2) and quantify its presence.Design Retrospective review of preoperative CT imaging.Setting Tertiary referral center in the United Kingdom.Participants One hundred patients who underwent endoscopic transsphenoidal surgery for pituitary disease were enrolled.Main Outcome Measure The presence and grading of the “teddy bear” sign were assessed on preoperative CT imaging.Results A grade 2 (strongly positive) “teddy bear” sign was identified in 40% at the level of the superior pituitary fossa, 78% at the inferior pituitary fossa, and 59% at the clivus. A grade 1 (intermediate) sign was seen in 23.5, 7.5, and 10% of cases, respectively. In 5% of cases, the sign was grade 0 at all levels—indicating poor intraoperative localization of the ICA.Conclusion The “teddy bear” sign is a useful preoperative tool for identification of anatomy predisposing patients to a higher risk of ICA injury. Those patients who have an absent or grade 0 “teddy bear” sign require extra care to ensure intraoperative localization of the ICAs which may include the use of neuronavigation or a Doppler probe. A grade 2 sign predicts good intraoperative localization of the ICA intraoperatively to inform the safe lateral limit of sellar bone resection.
Keywords: pituitary disease; pituitary gland; sella bone; sphenoid sinus; endoscopic; paranasal; sella turcica; carotid artery; internal